The ceramifying process and mechanical properties of silicone rubber/ ammonium polyphosphate/ aluminium hydroxide/ mica composites. (April 2016) - Hu, Sheng; Chen, Fei; Li, Jun-Guo; Shen, Qiang; Huang, Zhi-Xiong; Zhang, Lian-Meng
Abstract: The ceramifying process and mechanical properties of silicone rubber/ammonium polyphosphate/aluminium hydroxide/mica composites (hereinafter referred to as SRAAM) are investigated. The changes in microstructures and phase compositions of SRAAM during ceramifying process at different calcined temperatures are studied. At 300 °C, SRAAM residues exhibit porous structure due to gas evolution from the thermal decomposition of APP, Al(OH)3 and silicone rubber, but mica does not react with them. Although the flexural strength of SRAAM residues are low, the generation of aluminium phosphate (AlPO4 ) and NH4 AlP2 O7 improves the self-supporting. With no new phase generated, SRAAM residues maintain certain degree flexural strength due to the adhesive effection of aluminium phosphate during 300–600 °C. The reactivity of mica is increased by eliminating hydroxyl at temperature up to 800 °C, and then the chemically interactions between active mica and phosphates are able to generate Al2 O3 ·2SiO2, and KAlP2 O7 compounds improving the flexural strength. Further reactions between mica and KAlP2 O7 could generate KAlSi3 O8 at 1000 °C and the density of residual product is improved by low melting point phosphate filling pore to form relatively dense structure increasing the flexural strength. SRAAM with high flexural strength and good self-supporting from low to high temperatures is expected to be a kind of excellent ceramifying performance of flame retardant materials.